Impact of psychostimulants on microbiota and short-chain fatty acids alterations in children with attention-deficit/hyperactivity disorder - Nonglak Boonchooduang; Orawan Louthrenoo; Narueporn Likhitweerawong; Chanon Kunasol; Chanisa Thonusin; Sirawit Sriwichaiin; Wichwara Nawara; Nipon Chattipakorn; Siriporn C. Chattipakorn (Scientific Reports)
Abstract Attention-deficit/hyperactivity disorder (ADHD), a common neurodevelopmental disorder in children, is associated with alterations in gut microbiota and short-chain fatty acids (SCFAs), which are metabolites influencing the gut-brain axis. Evidence suggests that psychostimulant medications, widely used to manage ADHD symptoms, may also impact gut microbiota composition and SCFA levels. This study explores these potential effects by examining gut microbiota profiles and SCFA concentrations in unmedicated and medicated children with ADHD, compared to healthy controls. Fecal samples from 30 children aged 6–12 years (10 unmedicated ADHD, 10 medicated ADHD, and 10 healthy controls) were analyzed using 16 S rRNA sequencing and targeted metabolomics. Unmedicated ADHD children show distinct gut microbiota profiles, with lower level of Tyzzerella, Prevotellaceae, and Coriobacteriaceae, compared to controls. Notably, propionic acid levels were negatively associated with ADHD symptom severity, suggesting a potential biomarker role. Medicated ADHD children showed lower gut microbial diversity, unique taxa, and lower SCFA levels, compared to unmedicated children with ADHD. These findings suggest that gut microbiota and SCFAs may be linked to ADHD symptomatology, underscoring the importance of gut-brain interactions in ADHD. This study highlights the potential of gut health monitoring as part of future ADHD management strategies.